SIMULASI DAN ANALISIS HANDLING PERFORMANCE KENDARAAN JALAN RAYA JENIS SUV DENGAN SOFTWARE CARSIM 4.51 - Setiyana, Budi; Setiawan, Joga Dharma (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2010)
The latest progress in automotive industry development is increasing significantly therefore it also triggering the competition between road vehicle developers to build cars with variation in design, type, and specification to satisfy the customers in safety and comforts and also the performance. This report is trying to find out factors that affect the handling performance of a road vehicle and the turning behavior that appears while cornering, using two 98’ Jeep Grand Cherokee test vehicle. Simulation was conducted using CarSim Ed 4.51 software and taking case of Fishhook maneuver which is based on roll natural frequency and J-Turn maneuver without pulse braking. The result of the test is compared each other such that the factors affecting the turning behavior can be analyzed